Novel techniques to improve downlink multiple access capacity for Beyond 3G. (IEEE Communications magazine)
In future public mobile access with high data rates, one of the main challenges we face is spectral efficiency. In this article we will focus on the following new spectrally efficient downlink multiple access techniques that may be essential parts of China's Beyond 3G system development: dynamic code-division multiplexing, an adaptive multi-input multi-output technique in distributed wireless communications systems, and interleaver pattern division multi-access.